Environmental Ethics and Environmental Governance for Security in Africa - Ikeke, Mark Omorovie (European Journal of Sustainable Development, 2020)
The paper argues that an important aspect of security is environmental security. Without environmental security every other form of security is impeded. There need to be effective environmental governance if there is to be stable environmental security. The paper equally argues that environmental governance should be based on non-anthropocentric environmental ethics. Environmental governance is here understood to imply bringing human and governmental policies and legal frameworks to bear on the management of environmental resources. All over Africa there are a lot of environmental problems such as resource conflicts, climate change, desertification, deforestation, gas flaring, etc. These problems have to be eradicated for the good of the biotic community. This is why the paper is advocating for non-anthropocentric environmental ethics. The paper uses critical hermeneutic/analytic methods to examine the issues. The paper concludes that environmental governance informed by non-anthropocentric environmental ethics is a quintessential for security of lives/ properties in Africa. Keywords: Environment, ethics, security, governance, environmental ethics, environmental security, environmental governance, and Africa